Metabolic Reprogramming is a Hallmark of Metabolism Itself - Medina-Torres, Miguel Ángel (My University, 2020)
The reprogramming of metabolism has been identified as one of the hallmarks of cancer. It is becoming more and more frequent to connect other diseases with metabolic reprogramming. This article aims to argue that metabolic reprogramming is not driven by disease but instead is the main hallmark of metabolism, based on its dynamic behavior that allows it to continuously adapt to changes in the internal and external conditions.
Versión preprint del manuscrito del autor, publicado finalmente en: BioEssays 2020, 2000058; con DOI: 10.1002/bies.202000058
Keywords: Metabolismo; Metabolic reprograming